UNCOVERING THE DETERMINANTS OF MSME EMPLOYEE PERFORMANCE FROM THE PERSPECTIVE OF HUMAN RESOURCES, BUSINESS, AND ECONOMICS - Syaiful Amri; Topan Siswanto; Satriawan Satriawan; Rizka Oktaviana (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2026)
This study aims to analyze the determinants of employee performance in Micro, Small, and Medium Enterprises (MSMEs) in the Province of West Nusa Tenggara (NTB) by integrating perspectives from Human Resource Management (HRM), business, economics, and entrepreneurship. The variables examined include Ability, Motivation, Opportunity, Human Capital, and Business Strategy Alignment in relation to Employee Performance. A quantitative survey design was employed, and multiple linear regression was used to test the hypotheses. Data were collected from 200 MSME employees using a five-point Likert scale questionnaire. Instrument validity was assessed using Pearson Product-Moment correlation, while reliability was measured through Cronbach’s Alpha coefficients exceeding 0.70, indicating good internal consistency. The findings reveal that all independent variables have positive and significant effects on employee performance, both partially and simultaneously. Motivation emerged as the most dominant determinant, followed by Ability, Human Capital, Business Strategy Alignment, and Opportunity. The coefficient of determination (R²) indicates that the model explains a substantial proportion of the variance in employee performance. This study contributes theoretically by reinforcing the Ability–Motivation–Opportunity (AMO) framework and integrating economic and entrepreneurial perspectives within the MSME context. Practically, the findings have strategic implications for MSME managers and policymakers seeking to enhance human resource development to improve productivity and competitiveness